Unraveling Microbial Endosymbiosis Dynamics in Plant-Parasitic Nematodes with a Genome Skimming Strategy - Sulochana K. Wasala; Cedar Hesse; Catherine L. Wram; Dana K. Howe; Inga A. Zasada; Dee R. Denver (Applied Microbiology, 2023)
Bacterial endosymbionts, in genera Wolbachia and Cardinium, infect various arthropods and some nematode groups. Manipulating these microbial symbionts presents a promising biocontrol strategy for managing disease-causing parasites. However, the diversity of Wolbachia and Cardinium in nematodes remains unclear. This study employed a genome skimming strategy to uncover their occurrence in plant-parasitic nematodes, analyzing 52 populations of 12 species. A metagenome analysis revealed varying endosymbiont genome content, leading to the categorization of strong, weak, and no evidence for endosymbiont genomes. Strong evidence for Wolbachia was found in five populations, and for Cardinium in one population, suggesting a limited occurrence. Strong Wolbachia evidence was noted in Pratylenchus penetrans and Radopholus similis from North/South America and Africa. Heterodera glycines from North America showed strong Cardinium evidence. Weak genomic evidence for Wolbachia was observed in Globodera pallida, Meloidogyne incognita, Rotylenchus reniformis, Pratylechus coffeae, Pratylenchus neglectus, and Pratylenchus thornei; for Cardinium was found in G. pallida, R. reniformis and P. neglectus; 27/52 populations exhibited no endosymbiont evidence. Wolbachia and Cardinium presence varied within nematode species, suggesting non-obligate mutualism. Wolbachia and Cardinium genomes differed among nematode species, indicating potential species-specific functionality. This study advances knowledge of plant-parasitic nematode–bacteria symbiosis, providing insights for downstream eco-friendly biocontrol strategies.